2020
DOI: 10.1063/5.0006006
|View full text |Cite
|
Sign up to set email alerts
|

Optical response of nickel-based superalloy Inconel-718 for applications in additive manufacturing

Abstract: We present a broadband infrared and optical study of the compositionally complex nickel-based superalloy Inconel-718, a common material used in additive manufacturing using the direct metal laser sintering (DMLS) technique. We find a broad, featureless spectral emissivity, which is consistent with dc transport measurements and contextualize the results against literature reports of disordered metals. We show that electronic structure calculations based on first-principles modeling can explain most of the spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…However, to the best of the authors' knowledge, these optical properties are not reported in the literature. Consequently, in accordance with the experimental data provided in Figure 2(a) of (Curry et al, 2020), the real and imaginary parts of the dielectric function, e 1 and e 2 , corresponding to a Nd:YAG laser with a wavelength of 1,064 nm were extracted as À18.6 and 39.7, respectively. Accordingly, the ordinary refractive index and extinction coefficient of IN718 was estimated as (Fox, 2002).…”
Section: Powder Bed and Monte Carlo Ray-tracing Simulationsupporting
confidence: 59%
See 1 more Smart Citation
“…However, to the best of the authors' knowledge, these optical properties are not reported in the literature. Consequently, in accordance with the experimental data provided in Figure 2(a) of (Curry et al, 2020), the real and imaginary parts of the dielectric function, e 1 and e 2 , corresponding to a Nd:YAG laser with a wavelength of 1,064 nm were extracted as À18.6 and 39.7, respectively. Accordingly, the ordinary refractive index and extinction coefficient of IN718 was estimated as (Fox, 2002).…”
Section: Powder Bed and Monte Carlo Ray-tracing Simulationsupporting
confidence: 59%
“…New features of the proposed framework in comparison with previous works (Bajaj et al, 2019;Yadroitsev et al, 2015;Kamath, 2016;Mirkoohi et al, 2018;Boley et al, 2015) are briefly introduced as follows. The refractive index of IN718 material is not available, thus the measurement results of dielectric functions attained from literature (Curry et al, 2020) were used to calculate the refractive index of this material in the micro-scale model. Additionally, the processing maps of laser power and scanning speed corresponding to the different temperature of the solidified layer beneath the powder bed is constructed.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of DFT for materials properties that are determined at the electronic and atomic levels has been well tested; it provides a platform to bridge the gap between fundamental theory, high-throughput computational data science, and experiments [29][30][31][32][33][34][35][36][37] . Here, we perform first-principles calculations with DFT using the plane-wave pseudopotential method 38 .…”
Section: First Principles (Dft) Validationmentioning
confidence: 99%
“…[41] A recent study focused on radiative cooling in DED-AM and obtained the dielectric constant of the nickel-based superalloy Inconel-718 via experiments as well as DFT calculations to determine the spectral reflectivity and emissivity. [42] Due to the generality of the DFT calculation, these reported methods can be applied to a large variety of materials and can be readily turned into tools for materials design and quality control for AM.…”
Section: Dft and High-throughput Dftmentioning
confidence: 99%